Photoelectrode for water decomposition and its manufacturing method

KR103019757B1Active Publication Date: 2026-09-16KOREA UNIV RES & BUSINESS FOUND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020230042206
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2026-09-16
Estimated Expiration
2043-03-30

Smart Images

  • Figure 112023036188106-PAT00003_ABST
    Figure 112023036188106-PAT00003_ABST
Patent Text Reader

Abstract

The present invention discloses a photoelectrode for water splitting and a method for manufacturing the same, comprising: a substrate; an n-type semiconductor layer formed on the substrate; and a metal layered double hydroxide layer formed on the n-type semiconductor layer. The photoelectrode for water splitting according to the present invention may exhibit high surface reactivity to water oxidation as it has a high specific surface area, and may exhibit improved electrical conductivity and photoelectrode efficiency as it forms a heterojunction.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a photoelectrode for water splitting and a method for manufacturing the same, and specifically, to a photoelectrode for water splitting usable for photoelectrochemical water splitting and a method for manufacturing the same. Background Technology

[0002] Since the Industrial Revolution, the use of fossil fuels has been increasing explosively due to the skyrocketing demand for energy. This excessive consumption of fossil fuels releases harmful gases into the atmosphere—such as nitrogen oxides, sulfur dioxide, carbon dioxide, and carbon monoxide—causing environmental pollution and respiratory diseases, while also accelerating global warming caused by carbon dioxide emissions. Therefore, the development of new and renewable energy sources, such as solar, wind, hydrogen, and fuel cells, is necessary to replace fossil fuels. In particular, hydrogen energy is classified as an eco-friendly clean energy resource because it has a higher energy density (~120 MJ / kg) than fossil fuels, is non-toxic, and does not generate pollutants during combustion reactions. Hydrogen is found in water and hydrocarbons, which are the most abundant atoms on Earth. Consequently, hydrogen energy can be utilized as a sustainable energy resource as it allows for large-scale, continuous production and processing from various sources.

[0003] Hydrogen energy is produced through various methods, such as steam reforming of natural gas, pyrolysis of water, electrolysis of water, and photoelectrochemical water splitting processes.

[0004] Photoelectrochemical water splitting is an eco-friendly approach for producing hydrogen from water and solar energy, and interest in this method, which can minimize greenhouse gas emissions, is growing as environmental pollution issues increase. To achieve effective water splitting, various metal oxides such as TiO2, Fe2O3, WO3, ZnO, and BiVO4, and particularly n-type semiconductors, are being utilized as photocathode materials.

[0005] Among these, BiVO4, a monoclinic schelite material, has been utilized as an excellent light absorber for photoelectrochemical water splitting due to its moderate band gap (2.4–2.5 eV), lack of self-oxidation, and high chemical stability against water oxidation. However, low electrical conductivity and slow hole transport rates for water oxidation hinder charge transport and separation, which have been pointed out as factors limiting the photoelectrochemical water splitting performance of BiVO4. The problem to be solved

[0006] The present invention was devised to solve the above-mentioned problems and aims to present a photoelectrode for water splitting that improves low electrical conductivity, low surface reactivity, and charge transport and separation in a photoelectrode comprising an n-type semiconductor, and a method for manufacturing the same. means of solving the problem

[0007] As a means to achieve the above-mentioned purpose, the present invention provides a photoelectrode comprising: a substrate; an n-type semiconductor layer formed on the substrate; and a metal layered double hydroxide layer formed on the n-type semiconductor layer.

[0008] Here, the n-type semiconductor layer may be one or more materials selected from the group consisting of titanium oxide (TiO2), bismuth vanadate (BiVO4), indium oxide (In2O3), tungsten oxide (WO3), strontium titanate (SrTiO3) and hematite (Fe2O3).

[0009] Here, the metal layered double hydroxide layer is Ca 2+ , Mg 2+ , Zn 2+ , Ni 2+ , Mn 2+ , Co 2+ , Fe 2+ , Cu 2+ , Fe 3+ , Al 3+ , Cr 3+ , Mn 3+ , Ga 3+, Co 3+ and Ni 3+ It may include two or more metals selected from the group consisting of

[0010] Here, the metal layered double hydroxide layer may be formed from a metal-organic framework.

[0011] Here, the metal layered double hydroxide layer may include CoNi-layered double hydroxide.

[0012] Here, the n-type semiconductor layer and the metal layered double hydroxide layer may be type II heterojunctions.

[0013] In addition, the present invention provides a method for manufacturing a photoelectrode, comprising the steps of: forming an n-type semiconductor layer on a substrate; forming a metal-organic framework layer on the formed n-type semiconductor layer; and converting the metal-organic framework layer into a metal layered double hydroxide layer, as a means to achieve the above-mentioned objective.

[0014] Here, the metal-organic framework layer may include a positively charged metal-organic framework.

[0015] Here, the step of forming the n-type semiconductor layer can be performed according to one or more methods selected from the group consisting of physical vapor deposition, chemical vapor deposition, electrodeposition, and lamination.

[0016] Here, the step of forming the metal-organic framework layer can be performed according to one or more methods selected from the group consisting of dip coating, spray coating, and electroplating.

[0017] Here, the step of forming the metal-organic framework layer can be performed for 40 to 90 minutes.

[0018] Here, the metal-organic framework layer can be formed with a thickness of 5 to 20 nm.

[0019] Here, the step of converting the metal-organic framework layer into a metal layered double hydroxide layer can be performed according to one or more methods selected from the group consisting of solvothermal synthesis, hydrothermal synthesis, room temperature synthesis, ionothermal synthesis, and sonic chemical synthesis. Effects of the invention

[0020] The photoelectrode for water splitting of the present invention can exhibit high surface reactivity for water oxidation as it has a high specific surface area.

[0021] In addition, the photoelectrode for water splitting of the present invention can exhibit improved electrical conductivity and photoelectrode efficiency by forming a heterojunction. Brief explanation of the drawing

[0022] FIG. 1 is an energy band diagram of the interface between a metal layered double hydroxide layer (e.g., CoNi-layered double hydroxide) and an n-type semiconductor layer (e.g., BiVO4) according to the present invention. Figure 2 is an SEM and TEM image of the photoelectrode for water splitting according to the present invention. FIG. 3 is a flowchart showing the manufacturing process of the photoelectrode for water splitting according to the present invention. Figure 4 shows the HRTEM image and elemental analysis results of a photoelectrode for water splitting manufactured according to one embodiment of the present invention. Figure 5 is an XRD spectrum of a photoelectrode for water splitting manufactured according to one embodiment of the present invention. Figure 6 is a TEM image of a photoelectrode for water splitting manufactured according to one embodiment of the present invention. FIG. 7 is a graph showing the current density-voltage characteristics of a photoelectrode for water splitting manufactured according to one embodiment of the present invention. FIG. 8 is a graph showing the current density-voltage characteristics of a photoelectrode for water splitting manufactured according to one embodiment of the present invention. FIG. 9 is a graph showing the results of EIS analysis of a photoelectrode for water splitting manufactured according to one embodiment of the present invention. FIG. 10 is a graph showing the current density characteristics over time of a photoelectrode for water splitting manufactured according to one embodiment of the present invention. FIG. 11 is a graph showing the incident photon-electron conversion efficiency of a photoelectron for water splitting manufactured according to one embodiment of the present invention. Specific details for implementing the invention

[0023] The present invention is capable of various modifications and may have various embodiments, and specific embodiments are illustrated in the drawings and described in detail in the detailed description. However, this is not intended to limit the invention to specific embodiments, and it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.

[0024] Throughout this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0025] As used herein, terms of degree such as “about,” “substantially,” etc., are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the stated meaning, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosure in which precise or absolute values ​​are mentioned to aid in understanding the invention. Furthermore, throughout this specification, “a step of” or “a step of” does not mean “a step for”.

[0026] Since a person skilled in the art can make various applications through the gist of the present invention, the scope of the present invention is not limited to the following embodiments. The scope of the present invention extends to parts that are obvious to a person skilled in the art, based on the matters described in the patent claims, to be easily substituted or modified using prior art.

[0027] The present invention will be described in more detail below with reference to the attached drawings, where necessary.

[0029] Photoelectrode for water splitting

[0030] As a means to achieve the above-mentioned purpose, the present invention provides a photoelectrode comprising: a substrate; an n-type semiconductor layer formed on the substrate; and a metal layered double hydroxide layer formed on the n-type semiconductor layer.

[0031] The present invention relates to a photoelectrode used for photoelectrochemical (PEC) water splitting, wherein the basic principle of the PEC water splitting is to induce an electrochemical reaction by applying sunlight and an external bias to a photoreactive electrode immersed in an electrolyte containing an oxidation-reduction pair. The photoelectrode can absorb light to produce the energy required for the reaction, and additional energy is applied through the external bias to cause the overall water splitting reaction to occur.

[0032] When the above photoelectrode is an n-type semiconductor, oxygen is generated through an oxidation reaction at the photoelectrode, and hydrogen is generated through a reduction reaction at the counter electrode; when the photoelectrode is a p-type semiconductor, the opposite reaction occurs. In order to proceed with the photodecomposition of water without applying an external voltage, the band width of the semiconductor catalyst must be greater than the electrolytic voltage of water (theoretical value 1.23 V), and the valence band must be in a position positive to the O2 generation potential from water, and the conduction band must be in a position negative to the H2 generation potential. In addition, since the water splitting reaction mainly occurs in strong acid or strong base solutions, the stability of the photocatalyst must be guaranteed.

[0033] The n-type semiconductor layer satisfying the above-described conditions may be one or more materials selected from the group consisting of titanium oxide (TiO2), bismuth vanadate (BiVO4), indium oxide (In2O3), tungsten oxide (WO3), strontium titanate (SrTiO3), and hematite (Fe2O3), and according to one embodiment of the present invention, a more preferred example may be bismuth vanadate (BiVO4).

[0034] Accordingly, the inventors intended to improve the low electrical conductivity, low surface reactivity, and charge transport and separation of the n-type semiconductor layer by introducing a metal layered double hydroxide layer on the n-type semiconductor layer.

[0035] The above-mentioned layered double hydroxide (LDH) refers to a material with a double-layered structure capable of exchanging anions between layers, in which a divalent metal and a trivalent metal are included between the two layers of hydroxyl groups. Here, the metal layered double hydroxide layer is Ca 2+ , Mg 2+ , Zn 2+ , Ni 2+ , Mn 2+ , Co 2+ , Fe 2+ , Cu 2+ , Fe 3+ , Al 3+, Cr 3+ , Mn 3+ , Ga 3+ , Co 3+ and Ni 3+ It may include two or more metals selected from the group consisting of

[0036] Here, the metal layered double hydroxide layer may be formed from a metal-organic framework (MOF). In other words, the photoelectrode for water splitting according to the present invention may first form the metal-organic framework on an n-type semiconductor layer formed on a substrate, and then convert it into a metal layered double hydroxide layer.

[0037] The metal-organic framework mentioned above refers to a porous material in which metal ions or clusters containing metal are connected by organic ligands, and is a type of coordination polymer. Due to characteristics such as a large surface area, controllable porosity, and diversity of composition, such metal-organic frameworks can be used as suitable templates for layered double hydroxides (LDH). The layered double hydroxides are not only excellent water oxidation catalysts, but also have a high specific surface area derived from the metal-organic framework template, which can improve the insufficient surface reaction of the n-type semiconductor and increase the efficiency of water splitting.

[0038] The above metal-organic framework is not specifically limited to any particular type, and any metal-organic framework that can be synthesized at room temperature and carries a positive charge is acceptable. Specific examples of the above metal-organic framework may include Co-ZIF-L, etc.

[0039] According to one embodiment of the present invention, the metal layered double hydroxide layer may be, for example, a CoNi layered double hydroxide.

[0040] In semiconductors, a structure in which different semiconductor atoms constituting the matrix are joined is called a heterojunction, or in other words, a heterojunction. In a heterojunction, the band gap energies of the p and n regions differ, and since a high barrier is formed, carrier movement hardly occurs, allowing carriers to be controlled externally. The above heterojunction is classified into three types based on the energy state between the junction materials, specifically referred to as Type I, Type II, and Type III. Type I refers to a case where a narrow forbidden band is located within a wide forbidden band; Type II refers to a case where one band end is located within the other forbidden band (Staggered type); and Type III refers to a case where the forbidden bands of the two semiconductors do not overlap (Broken-gap type). In the present invention, the n-type semiconductor layer and the metal layered double hydroxide layer may be Type II heterojunctions.

[0041] FIG. 1 shows a metal layered double hydroxide (e.g., CoNi-layered double hydroxide) and an n-type semiconductor (e.g., BiVO) according to the present invention. 4) This is an energy band diagram of the interface. Referring to FIG. 1, the band end (E) of the CoNi-layered double hydroxide C It can be confirmed that a type II heterojunction is formed by the ) being located within the forbidden band of the above BiVO4 (Staggered type). In addition, it can be confirmed that as the above BiVO4 and CoNi-layered double hydroxide come into contact, an internal electric field is formed at the interface between the two, and holes and charges are separated.

[0042] FIG. 2 is an SEM and TEM image of the photoelectrode for water splitting according to the present invention. More specifically, FIG. 2a is an SEM image of the photoelectrode for water splitting according to the present invention, and FIG. 2b is a TEM image of the photoelectrode for water splitting according to the present invention. Referring to FIG. 2, it can be seen that the photoelectrode for water splitting according to the present invention has a metal layered double hydroxide layer formed on an n-type semiconductor layer, and the thickness is approximately 9.5 ± 3.5 nm.

[0043] The thickness of the metal layered double hydroxide layer is attributed to the thickness of the metal-organic framework, and in the step of forming the metal-organic framework layer on the n-type semiconductor layer, a difference in thickness occurs depending on the time taken to perform the aforementioned step. More specific details regarding the thickness of the metal layered double hydroxide layer (or the metal-organic framework) described above will be described in detail in the following <Method for Manufacturing a Photoelectrode for Water Splitting> and {Examples and Evaluation} sections.

[0045] Method for manufacturing a photoelectrode for water splitting

[0046] In addition, the present invention provides a method for manufacturing a photoelectrode for water splitting as a means to achieve the above-mentioned objective.

[0047] FIG. 3 is a flowchart illustrating the manufacturing process of a photoelectrode for water splitting according to the present invention. Referring to FIG. 3, it can be seen that the method for manufacturing a photoelectrode for water splitting according to the present invention comprises the steps of: forming an n-type semiconductor layer on a substrate; forming a metal-organic framework layer on the formed n-type semiconductor layer; and converting the metal-organic framework layer into a metal layered double hydroxide layer.

[0048] Here, the step of forming the n-type semiconductor layer may be performed according to one or more methods selected from the group consisting of physical vapor deposition, chemical vapor deposition, electrodeposition, and lamination, but is not limited thereto. Any method that does not cause a degradation in the performance of the substrate and the n-type semiconductor layer when the n-type semiconductor layer is formed on the substrate may be used. According to one embodiment of the present invention, the n-type semiconductor layer may be formed on the substrate through electrodeposition.

[0049] As described above, the metal-organic framework layer may include a positively charged metal-organic framework. The metal-organic framework can be synthesized at room temperature and may be any material as long as it carries a positive charge. As for the metal forming the metal-organic framework layer, Ca 2+ , Mg 2+ , Zn 2+ , Ni 2+ , Mn 2+ , Co 2+ , Fe 2+ , Cu 2+ , Fe 3+ , Al 3+ , Cr 3+ , Mn 3+ , Ga 3+ , Co 3+ , Ni 3+ It may include the like. According to one embodiment of the present invention, a specific example of the metal-organic framework may be Co-ZIF-L, but is not limited thereto.

[0050] Here, the step of forming the metal-organic framework layer may be performed according to one or more methods selected from the group consisting of dip coating, spray coating, and electroplating, but is not limited thereto. According to one embodiment of the present invention, in terms of ease of the metal-organic framework layer formation process and reduction of process costs, the metal-organic framework layer may be formed on the n-type semiconductor layer through a dip coating method.

[0051] Here, the step of forming the metal-organic framework layer can be performed for 40 to 90 minutes, preferably for 50 to 70 minutes, and more preferably for 55 to 65 minutes. By adjusting the time for forming the metal-organic framework layer, the thickness of the formed metal-organic framework layer can be controlled. More specifically, the shorter the time for performing the step, the thinner the metal-organic framework layer is formed, and the longer the time for performing the step, the thicker the metal-organic framework layer is formed. Therefore, if the time is less than 40 minutes, a sufficient amount of metal-organic framework layer is not introduced, which may result in problems where the electrical conductivity of the n-type semiconductor layer, low surface reactivity to water oxidation, and charge transport and separation are not improved. On the other hand, if the time exceeds 90 minutes, the metal-organic framework layer is formed too thickly, which may instead cause problems that hinder the photoreaction activity of the n-type semiconductor layer. Accordingly, the step of forming the metal-organic framework layer is preferably performed for 40 to 90 minutes.

[0052] Here, the metal-organic framework layer can be formed with a thickness of 5 to 20 nm. Preferably, it can be formed with a thickness of 6 to 15 nm, and more preferably, 7 to 12 nm. This thickness is determined by the time taken to form the metal-organic framework layer described above. If the metal-organic framework layer is formed to a thickness of less than 5 nm, problems may arise in which the electrical conductivity of the n-type semiconductor layer, low surface reactivity to water oxidation, and charge transport and separation are not improved; on the other hand, if the metal-organic framework layer is formed to a thickness exceeding 20 nm, problems may arise in which the photoreaction activity of the n-type semiconductor layer is hindered. Accordingly, it is preferable that the metal-organic framework layer be formed to a thickness of 5 to 20 nm.

[0053] Here, the step of converting the metal-organic framework layer into a metal layered double hydroxide layer may be performed according to one or more methods selected from the group consisting of solvothermal synthesis, hydrothermal synthesis, room temperature synthesis, ionothermal synthesis, and sonic chemical synthesis, but is not limited thereto.

[0054] Hereinafter, the claims of this specification will be explained in more detail with reference to the attached drawings and embodiments. However, as the drawings and embodiments presented in this specification may be modified in various ways by a person skilled in the art and may take various forms, the details described in this invention should not be limited to a specific disclosed form, but should be understood to include all equivalents and substitutions included within the spirit and technical scope of this invention. Furthermore, the attached drawings are presented to help a person skilled in the art understand the invention more accurately and may be depicted in an exaggerated or reduced size compared to the actual size.

[0056] {Examples and Evaluation}

[0057] <Example>

[0058] Example 1.

[0059] A porous BiVO4 thin film was formed on an FTO / glass substrate using a conventional synthesis method based on electrodeposition.

[0060] Next, 8.0 mmol of Co nitrate hexahydrate and 8.0 mmol of 2-methylimidazole were mixed in 30 mL of deionized water and stirred for 10 minutes to prepare a dip coating solution. Subsequently, Co-ZIF-L was coated onto a porous BiVO4 thin film using the dip coating method. The dip coating was performed for 60 minutes.

[0061] Next, 0.5 mmol of Ni nitrate hexahydrate was dissolved in 50 mL of ethanol. The above solution was transferred to a high-pressure hydrothermal autoclave, and a porous BiVO4 coated with Co-ZIF-L was placed therein. Subsequently, Co-ZIF-L was converted into CoNi-layered double hydroxide through a solvothermal reaction at 80 °C for 6 hours to prepare a BiVO4 electrode coated with CoNi-layered double hydroxide (hereinafter referred to as "Example 1").

[0063] Example 2.

[0064] A BiVO4 electrode coated with CoNi-layered double hydroxide was prepared in the same manner as in Example 1, except that the above dip coating was performed for 90 minutes (hereinafter referred to as "Example 2").

[0066] Comparative Example 1.

[0067] A BiVO4 electrode was prepared by forming a porous BiVO4 thin film on an FTO / glass substrate using a conventional synthesis method using electrodeposition (hereinafter referred to as "Comparative Example 1").

[0069] Comparative Example 2.

[0070] A BiVO4 electrode coated with CoNi-layered double hydroxide was prepared in the same manner as in Example 1, except that the above dip coating was performed for 3 minutes (hereinafter referred to as "Comparative Example 2").

[0072] Comparative Example 3.

[0073] A BiVO4 electrode coated with CoNi-layered double hydroxide was prepared in the same manner as in Example 1, except that the above dip coating was performed for 30 minutes (hereinafter referred to as "Comparative Example 3").

[0075] Comparative Example 4.

[0076] A porous BiVO4 thin film was formed on an FTO / glass substrate using a conventional synthesis method based on electrodeposition.

[0077] Next, 8.0 mmol of Co nitrate hexahydrate and 8.0 mmol of 2-methylimidazole were mixed in 30 mL of deionized water and stirred for 10 minutes to prepare a dip coating solution. Subsequently, Co-ZIF-L was coated onto a porous BiVO4 thin film using a dip coating method. At this time, the dip coating was performed for 60 minutes to prepare a BiVO4 electrode coated with Co-ZIF-L (hereinafter referred to as "Comparative Example 4").

[0079] The dip coating time, type and thickness of the formed layer of the above examples and comparative examples are summarized in Table 1 below.

[0080] division type Deep coating time Thickness (nm) Example 1 CoNi-layered double hydroxide 60 minutes 9.5 ± 3.5 Example 2 CoNi-layered double hydroxide 90 minutes 19.8 ± 9.1 Comparative Example 1 - 0 minutes - Comparative Example 2 CoNi-layered double hydroxide 3 minutes 3.2 ± 1.5 Comparative Example 3 CoNi-layered double hydroxide 30 minutes 5.1 ± 1.6 Comparative Example 4 Co-ZIF-L 60 minutes 9.0 ± 1.1

[0082] <Evaluation>

[0083] 1. Evaluation of Physical Properties

[0084] Figure 4 shows HRTEM images and elemental analysis results of a photoelectrode for water splitting prepared according to an embodiment of the present invention. More specifically, Figure 4a is a TEM image of Example 1, and Figures 4b to 4f show the distribution of bismuth (Bi), vanadium (V), oxygen (O), cobalt (Co), and nickel (Ni), respectively, in Example 1. In addition, the white dashed line indicates the interface between the n-type semiconductor layer (BiVO4) and the metal layered double hydroxide layer (CoNi-layered double hydroxide). Referring to Figure 4, it can be confirmed that the Co and Ni components are mostly distributed on the outer surface of BiVO4. This means that the metal layered double hydroxide layer is uniformly coated on the n-type semiconductor layer.

[0085] FIG. 5 is an XRD spectrum of a photoelectrode for water splitting prepared according to one embodiment of the present invention. Referring to FIG. 5, it can be seen that a peak (2θ = 11.1) corresponding to the (003) plane of the CoNi-layered double hydroxide layer appeared in Example 1. On the other hand, in Comparative Example 4, in which Co-ZIF-L was introduced onto the BiVO4 layer, the presence of such a peak could not be confirmed. Through this, it can be confirmed that in Example 1, the CoNi-layered double hydroxide layer was successfully introduced onto the BiVO4 layer through dip coating without changes in the crystal structure, etc.

[0086] FIG. 6 is a TEM image of a photoelectrode for water splitting prepared according to one embodiment of the present invention. More specifically, FIG. 6a is Comparative Example 1, FIG. 6b is Comparative Example 2, FIG. 6c is Example 1, and FIG. 6d is Example 2. Referring to FIG. 6, it can be seen that there is a difference in the thickness of the metal layered double hydroxide depending on the time for performing the dip coating, and it can be seen that the longer the dip coating time, the thicker the metal layered double hydroxide is formed.

[0088] 2. Evaluation of Photoelectrode Characteristics

[0089] FIG. 7 is a graph showing the current density-voltage characteristics of a photoelectrode for water splitting prepared according to one embodiment of the present invention. Referring to FIG. 7, Comparative Example 1 is 0.77 mA / cm² at the electrolytic voltage of water (theoretical value 1.23 V). 2 It can be confirmed that it exhibits a relatively low photocurrent density, and Example 1 (dip coating time = 60 min) showed the highest electrolytic voltage of water at 2.93 mA / cm². 2 It can be confirmed that it exhibits a photocurrent density. This photocurrent density value of Example 1 is approximately four times higher than that of Comparative Example 1. Furthermore, Example 2 (dip coating time = 90 min) shows approximately 2.5 mA / cm² at the electrolytic voltage of water. 2Although it exhibits a decent photocurrent density, it can be confirmed that it shows a lower value compared to Example 1 above. This suggests that when the dip coating time exceeds 90 minutes, the metal layered double hydroxide is formed excessively thickly, thereby hindering the photoreaction activity of the n-type semiconductor layer and reducing the PEC performance.

[0090] FIG. 8 is a graph showing the current density-voltage characteristics of a photoelectrode for water splitting prepared according to an embodiment of the present invention. More specifically, FIG. 8 shows the voltage value at which the water splitting reaction begins, and a lower voltage value indicates better catalytic characteristics. Referring to FIG. 8, it can be seen that the lowest voltage value is observed in Example 1 and the highest voltage value is observed in Comparative Example 1. In other words, it can be seen that the catalytic characteristics are best in Example 1, which exhibits the lowest voltage value.

[0091] FIG. 9 is a graph showing the results of EIS analysis of a photoelectrode for water splitting prepared according to an embodiment of the present invention. EIS refers to Electrochemical Impedance Spectroscopy, which measures resistance values ​​by applying an alternating current (AC) voltage. In the case of EIS analysis, it can be determined that the smaller the size of the semicircle, the better the catalytic characteristics. Referring to FIG. 9, it can be seen that Example 1 exhibits the smallest semicircle size, and Comparative Example 1 exhibits the largest semicircle size. In other words, it can be confirmed that Example 1, which exhibits the smallest semicircle size, has the best catalytic characteristics.

[0092] FIG. 10 is a graph showing the current density characteristics over time of a photoelectrode for water splitting prepared according to an embodiment of the present invention. Referring to FIG. 10, it can be seen that the current density of Example 1 exhibits the highest current density value over time, while Comparative Example 1 exhibits the lowest current density value. Furthermore, comparing the current density values ​​of Example 2 and Comparative Example 3, it can be seen that the two values ​​show similar current densities during a cycle of 0 to 200 sec; however, as the cycle progresses, the current density value of Comparative Example 3 gradually decreases, whereas Example 2 maintains approximately 2.25 mA / cm² even as the cycle progresses. 2 It can be confirmed that the current density value is maintained.

[0093] Figure 11 is a graph showing the incident photon-to-electron conversion efficiency of a photoelectrode for water splitting prepared according to an embodiment of the present invention. The light absorption and photoactivity of the photoelectron for water splitting of the present invention were investigated by evaluating the incident photon-to-electron conversion efficiency (IPCE) spectrum from 400 nm to 600 nm at 1.23 V versus RHE. Referring to Figure 11, Example 1 showed the highest IPCE of 55.9% at a wavelength of 460 nm, which can be confirmed to be four times higher than Comparative Example 1 (14.0%). In addition, the CoNi-layered double hydroxide layer BiVO It can be observed that the wavelength of the maximum IPCE (μmax) shifted slightly to a shorter wavelength from about 480 nm to about 460 nm as it was coated on the surface, which suggests that light absorption in the CoNi layered double hydroxide layer with a large band gap (~2.7 eV) contributed to the photoreaction of the electrode.

[0095] The photoelectrode for water splitting of the present invention can exhibit high surface reactivity for water oxidation as it has a high specific surface area.

[0096] In addition, the photoelectrode for water splitting of the present invention can exhibit improved electrical conductivity and photoelectrode efficiency by forming a heterojunction.

[0097] The above description is merely an illustrative explanation of the technical concept of the present invention, and those skilled in the art to which the present invention pertains will be able to make various modifications and variations within the scope of the essential characteristics of the present invention.

[0098] Accordingly, the embodiments disclosed in this invention are intended to illustrate, not limit, the technical concept of the invention, and the scope of the technical concept of the invention is not limited by these embodiments. The scope of protection of this invention shall be interpreted by the claims below, and all technical concepts within an equivalent scope shall be interpreted as being included within the scope of rights of this invention.

Claims

Claim 1 delete Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 A method for manufacturing a photoelectrode, comprising: a step of forming an n-type semiconductor layer on a substrate; a step of forming a metal-organic framework layer on the formed n-type semiconductor layer using a dip coating method; and a step of converting the metal-organic framework layer into a metal layered double hydroxide layer; wherein the dip coating method is performed for 60 to 90 minutes, and the thickness of the metal-organic framework layer is 5 to 20 nm. Claim 8 A method for manufacturing a photoelectrode according to claim 7, wherein the metal-organic framework layer comprises a positively charged metal-organic framework. Claim 9 A method for manufacturing a photoelectrode according to claim 7, wherein the step of forming the n-type semiconductor layer is performed according to one or more methods selected from the group consisting of physical vapor deposition, chemical vapor deposition, electrodeposition, and lamination. Claim 10 delete Claim 11 delete Claim 12 delete Claim 13 A method for manufacturing a photoelectrode according to claim 7, wherein the step of converting the metal-organic framework layer into a metal layered double hydroxide layer is performed according to one or more methods selected from the group consisting of solvothermal synthesis, hydrothermal synthesis, room temperature synthesis, ionothermal synthesis, and sonic chemical synthesis.

Citation Information

Patent Citations

  • Metal organic framework modified WO3 / W photo-anode film and preparation method and application thereof

    CN114108053A

  • Oxide film photoelectrode for reconstructing oxygen vacancy and preparation method thereof

    CN114921797A